Heat and mass transfer in three‐dimensional flow through a porous medium with periodic permeability. Issue 2 (22nd November 2018) - Ahmed, Nazibuddin; Choudhury, Kangkan
Abstract: In this paper, a theoretical study of a three‐dimensional mixed convective mass transfer flow past a semi‐infinite vertical plate embedded in a porous medium has been presented. The novelty of the present work is to analyze the influence of periodic permeability on the flow and transport characteristics in the presence of viscous dissipation and chemical reaction. The equations governing the flow, heat, and mass transfer are solved analytically by using asymptotic series expansion method. The variations in fluid velocity, temperature, and concentration fields due to change of various physical parameters are demonstrated graphically, whereas the numerical values of skin friction and the rate of mass transfer at the plate are compiled in tabular form. It is found that fluid velocity is increased for increasing permeability. Further, it is seen that concentration level of the fluid drops due to chemical reaction.